Lightweight design of an automobile hinge component using glass fiber polyamide composites - Güler, Taner; Demirci, Emre; Yıldız, Ali Rıza; Yavuz, Uğur (Carl Hanser Verlag, 2018)
In recent years, there has been a great deal of interest in lightweight vehicle design due to regulations about reducing fuel consumption and emissions. Lightweight design of vehicle components is one of the most important research topics in vehicle design. Developing the optimum structure in the early stages of design process is very important for minimizing the vehicle weight and production costs. In this paper, an automobile hinge component has been developed using PA66 GF60 glass fiber-reinforced polyamide composite materials instead of conventional steel. The automobile hinge component has been conceived using computer aided design software. Topology optimization was made under specific loadings subject to the constraints of finite element method analysis. As a result of this study, optimum dimensions of the component have been obtained and the weight of the component has been reduced via structural topology optimization techniques while satisfying displacement and stress conditions. The results show that composite materials are an important alterative in lightweight vehicle design.
Keywords: Composite; PA66 GF60; topology optimization; hinge; weight reduction; polyamide